Adverse drug reactions in psychiatry outpatient department of a tertiary care hospital in Western Uttar Pradesh: An observational study - Jaspreet Kaur Sidhu; Kiran Jakhar; Deepti Chopra; Aditi Dhote; Vishakha Babber; Mohammad Shadman; C D Tripathi (Wolters Kluwer Medknow Publications, 2022)
Objective: Psychiatric disorders are chronic in nature which require medications for a long duration. These medications have been associated with many adverse events. Failure to recognize an adverse drug reaction (ADR) exposes the patient to continuing risk of ADR, leading to a significant impact on patient's quality of life. Thus, the present study carried out to identify the pattern of ADRs reported due to psychotropic medication. Methods: This was a cross-sectional study conducted to analyze ADRs reported from the psychiatry department of a tertiary care teaching hospital from October 2021 to March 2022. Findings: A total of 137 ADRs were identified from 102 patients. Majority of the ADRs were reported from antidepressants, with paroxetine being the leading offending drug. The central nervous system was most commonly affected, and dizziness (13.13%) was the most common ADR noted. On causality assessment, 97 ADRs (70.8%) were of "possible" type. Almost half of the patients with ADRs (47.5%) recovered spontaneously. No ADR encountered turned out to be fatal. Conclusion: The present study revealed that the majority of ADRs reported from psychiatry OPD were mild in nature. We reinforce the identification of ADR is crucial in the hospital setting process as it gives an insight into the risk-benefit ratio for rational use of the drug.